2017
DOI: 10.1080/17405629.2017.1360177
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Malaysian adolescents: Validation of the IRPA self-report to measure reactive and proactive aggression

Abstract: leiden university, leiden, the netherlands; b human Development and family studies, university putra malaysia, serdang, selangor, malaysia; c center for group Dynamics, university of michigan, ann arbor, mI, usa; d Department of psychology, utrecht university, utrecht, the netherlands; e Dutch foundation for the Deaf and hard of hearing child, amsterdam, the netherlands;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…For instance, boys are found to be more physically aggressive than girls, but girls are found to be angrier than boys in a study carried out among primary school children in Malaysia (Kong et al, 2012). In contrast to another study, boys scored high on aggression that was associated with anger (Azam et al, 2019). Meanwhile, a study also found that boys are more likely to exert direct aggression after being victimized by direct aggression while girls are more likely to exhibit indirect aggression after being victimized by indirect aggression (Lundh et al, 2014).…”
Section: Limitations and Future Researchcontrasting
confidence: 71%
See 2 more Smart Citations
“…For instance, boys are found to be more physically aggressive than girls, but girls are found to be angrier than boys in a study carried out among primary school children in Malaysia (Kong et al, 2012). In contrast to another study, boys scored high on aggression that was associated with anger (Azam et al, 2019). Meanwhile, a study also found that boys are more likely to exert direct aggression after being victimized by direct aggression while girls are more likely to exhibit indirect aggression after being victimized by indirect aggression (Lundh et al, 2014).…”
Section: Limitations and Future Researchcontrasting
confidence: 71%
“…Proactive aggression is the instrumental, goal-directed behavior(s) aimed at harming others (Fanti, Frick, & Georgiou, 2009). Reactive aggression is the defensive behavior(s) aimed at protecting oneself against being aggressed by others (Azam, Novin, Oosterveld, & Rieffe, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have confirmed that adolescents are more likely to be the perpetrators of various forms of violent and aggressive behaviour including bullying, cyberbullying, dating violence, physical assault, and rape (Babore, Carlucci, Cataldi, Phares, & Trumello, 2017; Burton, 2008 Malcolm-Smith, Woolley, & Ward, 2015). Although aggressive behaviour among adolescents is common globally, several studies have indicated that the prevalence of aggression among adolescents in developing contexts is higher than in developed countries (e.g., Akiba, LeTendre, Baker, & Goesling, 2002; Dahamat, Novin, Oosterveld, & Rieffe, 2017).…”
mentioning
confidence: 99%